2015
DOI: 10.1080/0092623x.2015.1074133
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Supportive Interventions Targeting Individuals or Couples Undergoing Infertility Treatment: Directions for the Development of Interventions

Abstract: The purpose of this systematic review is to explore the types, content, and outcomes of different psychosocial approaches used in existing interventions for infertile individuals or couples. Relevant intervention studies published in English between 2000 and 2014 were searched using the electronic databases MEDLINE, PsycINFO, and CINHAL Plus. A total of 23 articles were identified and included in this review. Cognitive behavioral therapy (CBT), acceptance and commitment therapy (ACT), and counseling were the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 53 publications
(43 reference statements)
0
23
0
1
Order By: Relevance
“…Furthermore, several studies have found that interventions focused on the acquisition of specific coping skills (Boivin, 2003) and broader support interventions (e.g. cognitive behavioural therapy and mind/body interventions) could benefit fertility patients in reducing psychological distress (Chow, Cheung, & Cheung, 2016;de Liz & Strauss, 2005;Frederiksen, Farver-Vestergaard, Skovgard, Ingerslev, & Zachariae, 2015;Luk & Loke, 2016). However, past interventions have mostly targeted patients after a cycle or when treatment ended; thus, future intervention studies may consider specific treatment stages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have found that interventions focused on the acquisition of specific coping skills (Boivin, 2003) and broader support interventions (e.g. cognitive behavioural therapy and mind/body interventions) could benefit fertility patients in reducing psychological distress (Chow, Cheung, & Cheung, 2016;de Liz & Strauss, 2005;Frederiksen, Farver-Vestergaard, Skovgard, Ingerslev, & Zachariae, 2015;Luk & Loke, 2016). However, past interventions have mostly targeted patients after a cycle or when treatment ended; thus, future intervention studies may consider specific treatment stages.…”
Section: Discussionmentioning
confidence: 99%
“…Infertility is defined as the lack of ability to achieve a clinical pregnancy after one year or more of unprotected and well-timed intercourse with the same partner [ 1 ]. It is estimated that around 15% of couples of reproductive age present with infertility, and about half of the infertility is associated with male partner [ 2 , 3 ]. With the continuing world-wide increase in male infertility, it has become a major health problem attracting more clinical attention.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is defined as the lack of ability to conceive within one year of unprotected intercourse with the same partner 1 . It is estimated that nearly 8–12% of couples are infertile 2 , and approximately 30–40% of infertility cases are caused by male factors 3 . Several risk factors are involved in the pathogenesis of infertility, some of which include alterations in spermatogenesis due to testicular cancer, aplasia of the germinal cells, varicocele, defects in the transport of sperm, or environmental factors as well as congenital anomalies, infectious diseases, bilateral spermaducts, pregnancy-related infections, alterations in the characteristics of semen such as a decrease in sperm motility and sperm count, the presence of antisperm antibodies (ASAs), and nutritional deficiency of trace elements such as selenium and zinc (Zn) 4 5 6 7 8 9 .…”
mentioning
confidence: 99%